Understanding power, politics, and organizational culture in order to effectively develop interdisciplinary partnerships - Wendy Green; Catherine Hansman (Adult Education Research Conference, 2020)
There has been a consistent shift in how health professions education is viewed and a move to bring the fields of graduate medical education, continuing medical education, and adult education together in order to create more robust learning environments. We propose a conceptual model that addresses organizational differences and power dynamics that acknowledges how power, politics, organizational culture, team dynamics and individual interactions influence the development and implementation of health professions programs.